NK cell count and glucotransporter 4 (GLUT4) expression in subjects with type 2 diabetes and colon cancer. Issue 1 (December 2016) - Piątkiewicz, Paweł; Bernat-Karpińska, Małgorzata; Miłek, Tomasz; Rabijewski, Michał; Rosiak, Elżbieta
Abstract Background Type 2 diabetes (T2D) and colon cancer (CC) are numbered among the most common diseases in the world. The decreased activity of natural killer (NK) cells previously revealed in both mentioned pathological states may be correlated with impaired expression of GLUT4 as the major insulin-dependent glucose transporter in these cells. Methods The aim of this study was to evaluate GLUT4 expression and NK cells number in subjects with T2D and/or CC in comparison with control group. We evaluated 78 individuals divided into four groups: (1) patients with CC and T2DM, (2) patients with CC, (3) patients with T2DM (4) healthy control. GLUT4 expression on the surface of NK cells was measured using flow cytometry and phenotyping of NK cell was performed by immunofluorescent method. Results Subjects with diabetes had the highest GLUT4 expression (21.35 ± 7.2 %) in comparison with other groups (P  < 0.01). The mean values of GLUT4 expression in group with CC and in patients with both T2D and CC were similar (1.4 ± 0.4 % vs 1.5 ± 1.0 %; respectively). These values were significantly lower than in control group (12.6 ± 2.9 %;P  < 0.01). In patients with T2D and CC the number of NK cells (20.15 ± 6.6 %) was significantly higher than in other groups, i.e. in group with T2D (14.08 ± 5.7 %), in group with CC (9.21 ± 3.6 %) and in control group (9.48 ± 4.7 %), respectively (P  < 0.01). Conclusions It seems that there is a need to pay more attention to the high incidence of colon cancer among patients with type 2 diabetes. Decreased GLUT4 expression observed on NK cells in patients with colon cancer may be responsible for dysfunction of these cells and the higher carcinogenic risk in type 2 diabetic subjects.